2017
DOI: 10.1111/prd.12150
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of peri‐implant and periodontal marginal soft tissues in health and disease

Abstract: The integrity of the peri-implant soft-tissue seal is crucial for maintaining peri-implant tissue health. Whilst the transmucosal component of the restored implant shares some common features with teeth, namely the presence of a junctional epithelium and a connective tissue component, there are some important differences. A key difference is the nature of the relationship of the connective tissue with the implant surface, whereby there is 'adaptation' of collagen fibers in a parallel orientation in relation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
141
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(167 citation statements)
references
References 89 publications
(144 reference statements)
2
141
1
2
Order By: Relevance
“…This could be due to the internally relocated implant‐abutment junction, which limits peri‐implant bone loss by moving bacteria and inflammatory cells away from the adjacent crestal bone . It is important to emphasize that the characteristics of the implant design, the nature of the connection between the implant and the abutment, as well as the characteristics of the abutment and the implant surface, can influence the maintenance of soft tissue integrity around the implants …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due to the internally relocated implant‐abutment junction, which limits peri‐implant bone loss by moving bacteria and inflammatory cells away from the adjacent crestal bone . It is important to emphasize that the characteristics of the implant design, the nature of the connection between the implant and the abutment, as well as the characteristics of the abutment and the implant surface, can influence the maintenance of soft tissue integrity around the implants …”
Section: Introductionmentioning
confidence: 99%
“…7 It is important to emphasize that the characteristics of the implant design, the nature of the connection between the implant and the abutment, as well as the characteristics of the abutment and the implant surface, can influence the maintenance of soft tissue integrity around the implants. 8 The term "biological width" was introduced by Gargulio et al in 1961. 9 Several authors have verified that biological width also exists around implants.…”
mentioning
confidence: 99%
“…For example, Buser et al [56] reported that collagen fibers in soft tissue were oriented parallel to the implant although a direct soft-tissue contact has been observed to smoothly polished sandblasted titanium surfaces. It is thought that the difference in the orientation of collagen fibers is one of the causes of peri-implantitis [57].…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, a new peri-implant epithelium (PIE) forms around a dental implant, but we hypothesize that it is not functionally equivalent to the native JE. Published data (and also reviewed in Atsuta et al, 2005;Ivanovski & Lee, 2018) claim that the PIE shares structural, ultrastructural, and functional characteristics with the JE, but obvious differences such as the morphology (Heyman et al, 2018) and mitotic activity (Fujiseki et al, 2003) are demonstrated to exist between PIE and JE. Another difference is the pattern and onset of Laminin 5 expression following implant placement, which was both delayed and inconsistent within the PIE (Atsuta et al, 2005).…”
Section: Does a Functional Je-like Structure Reform Around A Dentalmentioning
confidence: 99%